DYNAMIC SIMULATION AND FLEXIBLE ROTOR BALANCING IN N-TH BEND SHAPE - Oleg O. Polushkin; Oleg A. Polushkin (Advanced Engineering Research)
Some mechanisms of determining the flexible rotor axis elastic buckling in the eigenmode bend and thereto related distributed unbalances are specified through its dynamic simulation. A new method of identifying the model parameters and balancing of such rotors in the eigenmode bend is evolved.